Magnetostratigraphy of ODP Leg 107 holes - James E T Channell; Masayuki Torii; Teresa B Hawthorne (PANGAEA, 1990)
Apart from Site 650, core disturbance due to rotary drilling severely compromised the quality of the magnetostratigraphic data obtained from Leg 107 sediments. The correlation of polarity zones to the geomagnetic polarity time scale cannot be made solely on the basis of pattern fit. The proposed correlations are consistent between sites, and this consistency is constrained by the biostratigraphic datums. The resulting biomagnetostratigraphic correlations are reviewed in the synthesis section of this volume. The purpose of this paper is to document the magnetic stratigraphies, and present the preferred correlation to the geomagnetic reversal time scale. Four implications of the proposed correlations are: (1) The Mio-Pliocene boundary occurs in the lowest reversed interval of the Gilbert (Chron 3r) at about 4.9 Ma. (2) The thick pre-Pliocene lacustrine sequence recovered at Site 652 appears to have been deposited entirely within a single reversed polarity chron (Chron 3r). (3) The balatino-type gypsum recovered at Site 654 was also deposited entirely within this polarity chron (Chron 3r). (4) The Tortonian-Messinian boundary occurs within a normal polarity zone which is probably correlative to Chron 6 (Chron 3B) giving a boundary age of about 6.4 Ma.
Supplement to: Channell, JET et al. (1990): Magnetostratigraphy of sediments recovered at sites 650, 651, 652 and 654 (Leg 107 in the Tyrrhenian Sea). In: Kastens, KA; Mascle, J; et al. (eds.), Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 107, 335-346, https://doi.org/10.2973/odp.proc.sr.107.167.1990